Working from self-driving cars - Georg Hirte; Renée Laes (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2022)
Once automatic vehicles are available, working from self-driving car (WFC) in the AV's mobile office will be a real option. It allows firms to socialize land costs for office space from the office lot to road infrastructure used by AV. Employees, in turn, can switch wasted commuting time into working hours and reduce daily time tied to working. We develop a microeconomic model of employer's offer and employees choice of WFC contracts and hours. Using data for Germany and the U.S., we perform Monte Carlo studies to assess whether WFC may become reality. Eventually, we study the impact of transport pricing on these choices. Our findings is, that WFC contracts are likely to be a standard feature of large cities given current wages, office, and current and expected travel costs. There is a clear decline of hours spent working in office. On average, WFC hours and distance traveled slightly exceed commuting figures.
urn:nbn:de:bsz:14-qucosa2-783738
Keywords: R40; R41; R48; 330; autonomous driving; telecommuting; working from car; working from home; transport economics